Effects of the Attention Training Technique on Auditory Hallucinations in Schizo-Affective Disorder: A Single Case Study. (9th August 2018) - Carter, Karin E. P.; Wells, Adrian
Abstract : A 41-year-old female with schizo-affective disorder presenting with an eight-year history of auditory hallucinations participated in a single case treatment study (A-B-A-B-A-C-B) of the effects of the Attention Training Technique (ATT). No antipsychotic medication was prescribed in this case following a serious adverse reaction in the past. The aim of the study was to test the impact of ATT on the frequency and duration of hallucinations using a repeated return to baseline followed by an alternating treatment design. The alternative intervention consisted of autogenic relaxation instructions. The patient monitored the frequency, duration, and her distress over the voices on a daily basis during baseline and intervention phases across a study period of 80 weeks. Visual analysis of the data showed that ATT when introduced at three phases following baselines or control conditions was associated with a reduction in auditory hallucination frequency and duration compared to the other phases. This contrasted with the autogenic relaxation intervention that was associated with an increase in duration and frequency of voices. The perceived benefits of ATT were maintained for varying periods of time.